Runx3 Mediates Resistance to Intracellular Bacterial Infection by Promoting IL12 Signaling in Group 1 ILC and NCR+ILC3 - Yin, Shengxia; Yu, Jingjing; Hu, Bian; Lu, Chenyu; Liu, Xia; Gao, Xianzhi; Li, Wei; Zhou, Lina; Wang, Jianli; Wang, Di; Lu, Linrong; Wang, Lie (Frontiers in Immunology, 2018)
Innate lymphoid cells (ILCs) are the most recently identified family of innate immune system and are believed to modulate immune functions prior to the generation of adaptive immune responses. While, subsets of ILCs reside in the mucosa and regulate immune responses to external pathogens, their role and mechanism in protecting against intracellular bacterial infection is incompletely understood. In this report, using S.Typhimurium and L. monocytogenes, we found that the level of group 1 ILCs and NCR+ ILC3s was increased upon infection, and that this was associated with Runt-related transcription factor 3 (Runx3) expression. Runx3 fl/fl PLZF-cre mice were much more sensitive to infections with the intracellular bacterial pathogens S.Typhimurium and L. monocytogenes due abnormal Group 1 ILC and NCR+ILC3 function. We also found that Runx3 directly binds to the Il12R2 promoter and to intron 8 to accelerate the expression of Il12R2 and modulate IFN secretion triggered by the IL12/ STAT4 axis. Thus, we demonstrate that Runx3 is influences group 1 ILC and NCR+ILC3-mediated immune protection to intracellular bacterial infections of both the in gut and the liver.